Code Mixing Employed by the English Lecturers in EFL Classroom - Asep Hardianto (Universitas Muhammadiyah Kotabumi, 2017)
The purpose of this research is to investigate the forms and factors influencing code mixing produced by lecturers. The data of this research is lecturers’ utterances during the subject of speaking and writing learning process in English education study program of STKIP Muhammadiyah Kotabumi. This research used descriptive qualitative method by sociolinguistic approach. The data of this research were recorded, analyzed, and interpreted descriptively. The research result showed that (1) There are four forms of code mixing found such as word, phrase, clause, and repetition word; (2) There are three factors influencing code mixing occurences such as identification of roles, variance identification, and limitation of language utterance. Furthermore, this article is expected to contribute the knowledge related code mixing studies for further research.